Leaf extract of Coffea arabica L. reduces lipid peroxidation and has anti-platelet effect in a rat dyslipidemia model - Mario Henrique Souza Simões; Bruno Cesar Correa Salles; Stella Maris da Silveira Duarte; Marcelo Aparecido da Silva; André Luiz Machado Viana; Gabriel de Oliveira Isaac de Moraes; Sonia Aparecida Figueiredo; Eric Batista Ferreira; Maria Rita Rodrigues; Fernanda Borges de Araújo Paula (Brazilian Journal of Pharmaceutical Sciences, 2022)
Abstract This study aimed to evaluate the antioxidant potential of the Coffea arabica Lineu (L.) leaf extract and its effects on platelet aggregation of dyslipidemic rats. The extract was obtained by the percolation of C. arabica L. leaves in hydroethanolic solution 70% (v/v). The mass spectrometry FIA-ESI-MS² suggested the presence of chlorogenic acid, rutin acid, and quinic acid. The DPPH• radicals scavenging capacity was demonstrated (IC50 = 0.06 mg/mL). The extract was administered to rats by gavage (300 mg/kg/day) for 56 days. Dyslipidemia was induced by administering Triton WR-1339 (300 mg/kg body weight) on the 54th day. On day 56, blood was collected by puncturing the abdominal aorta artery and the aortic artery was removed. Lipid profile, markers of renal and hepatic injury, lipid peroxidation, and platelet aggregation tests were carried out. The ingestion of extract reduced the lipid peroxidation (aorta and plasma) and platelet aggregation in dyslipidemic rats. The extract did not affect markers of renal and hepatic function as analyzed in this study, suggesting neither impaired liver nor kidney function in these animals. Therefore, our results demonstrate that the extract of leaves of C. arabica L. show antioxidant potential in vitro and in vivo as well as anti-platelet aggregation in dyslipidemic animals.